PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA SULTAN DRINK - Nirwana Sampara (Jurnal Projemen UNIPA, 2025)
This study aims to analyze the influence of service quality on customer satisfaction at Sultan Drink in Soreang District, Parepare City. Service quality is measured through five main dimensions: tangibles, reliability, responsiveness, assurance, and empathy. A quantitative approach was employed using a survey method, with data collected through questionnaires. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results show that both partially and simultaneously, all five dimensions of service quality have a significant influence on customer satisfaction. Among them, the reliability dimension has the most dominant effect. The coefficient of determination (R²) is 0.800, indicating that 80% of the variation in customer satisfaction can be explained by service quality, while the remaining 20% is influenced by other factors outside the model. These findings highlight the importance of improving overall service quality, particularly in reliability, to enhance and sustain customer satisfaction.